Penerapan Media Permen Fakta dan Opini Berbasis PBL untuk Meningkatkan Penalaran Kritis Siswa SD - Mutammimah, Laila Himmatul; Purwati, Panca Dewi (YASIN, 2025)
Although critical reasoning skills in distinguishing facts from opinions have been widely investigated, studies that specifically examine the integration of concrete media with the systematic steps of Problem-Based Learning (PBL) to strengthen elementary students’ analytical abilities remain limited. This study aims to analyze the effectiveness of the PBL-based Permen Fakta dan Opini medium in improving sixth-grade students’ critical reasoning skills. A mixed-methods approach with a Sequential Explanatory design was employed, beginning with a quantitative one-group pretest–posttest experiment involving 31 students selected through total sampling, followed by observations and interviews. Data were collected through a critical reasoning test, observation sheets, and interview protocols, and were analyzed using descriptive statistics, N-Gain calculations, and thematic analysis. The results show a significant increase in critical reasoning ability, as indicated by a rise in the mean score from 56.45 to 84.51 and an increase in mastery learning from 45.16% to 87.09%, with an N-Gain value of 0.66 indicating moderate-to-high improvement. Qualitative findings corroborate the quantitative results through evidence of increased participation, clearer argumentation, and greater consistency in classifying factual and opinion statements. This study contributes to the strengthening of constructivist theory by demonstrating that integrating concrete media with PBL can deepen conceptual understanding during analytical processes and underscores the importance of student-centered instructional strategies supported by concrete media to optimize higher-order thinking skills. Follow-up studies are recommended to examine long-term retention and to test the use of similar media in other content areas.